Anthropology in Dance: Gesture Systems of the Body - Ábrahám, Nóra (Ethnographica et Folkloristica Carpathica, 2021)
My paper outlines an anthropological approach to dance focusing on the body’s interpretation within the contexts of space, sensuality, theater, fashion, aesthetic quality, and the development of gesture systems of the body. The study addresses the question whether the bareness of the body and space may be defined as a form of emptiness or rather as a case of sincere manifestation and revolves around the issues of social and personal attitudes related to dance performance, including mimetic performers, limits of social body norms, and the possibilities of survival, especially the changes in the female body’s perceptual and social roles and strategies.